Proteomic tools to study drug function. Issue 10 (August 2018) - Mulder, Celine; Leijten, Niels; Lemeer, Simone
Abstract: With the ever growing repertoire of drugs being developed, new unbiased methods are urgently needed that allow fast screening of protein targets and off-targets. Ideally, these methods are capable of studying target engagement in a cellular context and provide a link between drug and cellular phenotype. Mass spectrometry based strategies provide an excellent way to study drug-target interactions as well as drug effects in a cellular context with excellent sensitivity and depth. In order to perform unbiased drug target screening several methods have been developed over the last years. In this review, we discuss affinity pull-down approaches to study direct drug-target interaction, methods which use alterations in protein stability as a measure for drug binding and the biological relevance of PTM enrichments to study the effect of inhibitors on cellular signalling. Highlights: Direct drug-target interactions studied by affinity pull down of interactors. Protein stability as a measure for ligand binding or complex formation. PTM enrichment to study influences of drugs on cell signalling.